Upaya Pembentukan Palestinian Unity Government - Abdullah, Abdullah; Fahirdan, Mohammad Ihza (Indonesia Center for Middle East Studies, 2023)
This article discusses the long efforts of reconciliation in Palestine between Hamas and Fatah that have been going on for the last decade but have not yet achieved the expected results. The agreed-upon agreements become formalities that stop at the negotiation stage, not yet at the implementation stage. This research focuses on efforts to form a Palestinian Unity Government after the 2017 Cairo Agreement during the 2017-2020 period. The concept used in the analysis is the concept of transitional justice, which is closely related to the issue of human rights. This study uses a descriptive-analytic method to examine variables relevant to the research objectives. The results of this study indicate that among the obstacles to establishing a Palestinian Unity Government is the incomplete accountability for human rights violations committed by the two groups against each other, the existence of mutual distrust of one another, and the exclusion of other factions from the reconciliation efforts.